Analisis Kepuasan Pelanggan (Customer Satisfaction) Terhadap Layanan Hypermart Pekanbaru - Alvi Furwanti Ahvie; Deny Danar Rahayu (Jurnal Ekonomi, 2009)
This paper investigated the customer ratings of importance of several attributesassociated with supermarket shopping. Then reviewed the satisfaction ratings of theattributes. The aim was to rank the factors and to relate the importance rankings tocustomer satisfaction. The findings have implications in that a retailer is able toassess how well they meet their customers needs on important attributes. The resultssuggested that since retail formats have become very standardized, corporatereputation is rated high and may be a source of sustainable competitive advantage.